ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN INOVASI KELUARGA SEHAT DI WILAYAH KERJA PUSKESMAS KALANGAN KABUPATEN TAPANULI TENGAH TAHUN 2018 - Manaluu, Elisabet; Sitorus, Friska (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
A healthy family can be said to be in a prosperous condition and condition. Physically, socially and mentally, it is possible to become a whole family consisting of individuals led by a family head and living in an environment so that they can live fairly, both economically and socially. This study aims to analyze the factors related to the application of healthy family innovation in the work area of ​​the South Tapanuli Kalangan Health Center. This type of research is quantitative using a cross sectional approach. The population in this study were all residents in the working area of ​​the Kalangan Health Center, namely Aek Garut Village and Sitio Tio Village. The study started from January to May 2018. The research sample was 127 people with simple random sampling. Data analysis includes univariate, bivariate to multivariate. The results showed that only 62.2% of respondents adopted a healthy family, while the factors of age, knowledge, planning, monitoring, facilities/infrastructure and organizational staff related to the implementation of healthy family innovation. It is recommended to the Health Office of Central Tapanuli to supervise and direct the community to implement a healthy family program by increasing the promotion and socialization of healthy families to the Posyandu level and cooperating with community leaders.